Photocatalysis Using Titanium Dioxide for Treatment of Textile Wastewater Containing Disperse Dyes - Shumaila Kiran (Science Faculty of Chiang Mai University, 2019)
Present research work was carried out to investigate the decolorization of synthetic textile wastewater using titanium dioxide as a photo-catalytic agent. Synthetic wastewater was prepared by mixing three disperse dyes. Samples were passed through artificial and solar-assisted photo-catalysis. Photo-catalytic treatment was evaluated with help of different parameters like dose of titanium dioxide (TiO2), concentration of synthetic dyes wastewater having disperse dyes, pH, concentration of hydrogen peroxide (H2O2), and temperature. Artificial photo-catalytic treatment was done using synthetic light lamp, with different light intensities and solar-assisted treatment was carried out at different times of day under optimized conditions. The different parameters were employed for water quality assurance such as total organic carbon (TOC) and chemical oxygen demand (COD). The maximum decolorization and mineralization was obtained with solar-assisted photo-catalysis treatment. The degradation products were studied using FTIR spectral studies.